Supplementary training for endurance sports optimize performance, avoid overloading - Luchtenberg, Dietmar (Meyer & Meyer Sport (UK) Ltd., 2008)
Endurance sports are an increasingly popular way of keeping fit. However, overtraining can cause physical symptoms of overloading. This work shows readers how to optimize their performance without experiencing these types of problems. It features targeted programmes composed of stretching, strengthening, co-ordination and relaxation exercises